“Obtención de una bebida energizante a base de borojó (Borojoa patinoi) y guanábana (Annona muricata)”. - Valle Velasco, Mario Santiago (2023)
The purpose of this project is to develop an energy drink based on borojó, soursop with the addition of the infusion of guayusa leaves and ginger extract, where the physical-chemical, nutritional, sensory and microbiological parameters of each one were determined. of the treatments. And of the sensory to determine the best treatment in which case the caffeine content in the drink was determined. It is worth mentioning that it started from the determination of the physical-chemical parameters of the borojó juices, guanábana that was obtained as preliminary data of the investigation. On the other hand, the study factors were A: proportion of the fruit, Factor B: concentration of the energizer based on ginger extract and Factor C: type of sweetener. For the elaboration of this drink, an experimental design was applied under an AXBXC factorial arrangement with a total of 16 treatments with three factors, two levels and two replicates. The best treatment t3(a1b2c1) was identified, whose factors were 300 g of soursop: 200 g of borojó + 12.5 g of the concentration of ginger extract + 0.625 g of edulmix, which was determined based on sensory analysis and whose Results were: acidity 0.67% (g/ml), pH 3.18, soluble solids 5.38%, vitamin C 110.40 mg/100 g, total alkaloids expressed as % caffeine 1.38% (g/ ml) and the microbiological analysis of both mesophilic aerobes and molds and yeasts was 0 UFC/ml and the caffeine content with a value of 286.66 mg/L. Finally, a balance of materials was made whose yield was 72.22%, which indicates this profitable food alternative for production and marketing.